P247 The Prevalence of Asthma and Level of Treatment in Current or Former Heroin Smokers. (12th November 2015) - Vlies, BH; Lewis-Burke, N; Davies, L; Walker, PP
Abstract : Introduction: We have reported an association between heroin smoking and early onset severe COPD/emphysema and from this screening study reported a COPD prevalence of approximately one third in heroin smokers attending a community drug centre. However, respiratory symptoms were common in people who did not have COPD and a previous report showed a high level of wheeze and bronchial hyper-responsiveness in opiate smokers/insufflators. Therefore, we examined our cohort to determine asthma prevalence and level of symptoms and treatment in this group. Methods: Current and former heroin smokers were recruited from a community-based drug service in Merseyside and completed spirometry with reversibility testing, MRC and CAT score and smoking, drug use, health and treatment questionnaires. They were not selected because of the presence of symptoms. Asthma was defined by either airflow obstruction that normalised with bronchodilation or airflow obstruction with an FEV1 that improved by ≥9% with bronchodilation (7 subjects), or a diagnosis of asthma before age 25 or before the subject had smoked heroin for 2 years (28 subjects). Results: 107 heroin smokers completed the study, the majority of whom had also smoked cigarettes, cannabis and crack. 35/107 (33%) met our diagnosis of asthma and we compared them with 42 heroin smokers with neither COPD nor asthma. The asthma subjects had a significantly lower mean FEV1 (3.26 L vs 3.73 L and 83% vs 97% predicted) and FEV1/FVC (0.71 vs 0.81). Mean age was 42 years and duration of cigarette, cannabis and crack smoking was similar as were MRC and CAT scores. Symptoms were very common in the asthma group – cough 23 (66%), wheeze 23 (66%) and breathlessness 26 (74%) but this was similar to the non-asthmatics. Only 11 (31%) were prescribed short-acting beta-agonists and/or inhaled steroids and only 2 (6%) a long-acting beta agonist despite 32 (92%) having a prior diagnosis of asthma. Conclusions: In an unselected group of current/former heroin smokers the prevalence of asthma was high at 33% and similar to the number diagnosed with COPD. Further detailed assessment of this cohort may be valuable and different methods of engaging with this undertreated and hard-to-reach group worthy of examination.